Modelling of the non-reactive deposits impact on centrifugal compressor aerothermo dynamic performance. (February 2016) - Al-Busaidi, Waleed; Pilidis, Pericles
Abstract: The centrifugal compressor blockage is considered an important issue in compressor operation and one of the main causes of machine failure. This is normally initiated by the presence of deposits with the process gas yielding to reduce the effective flow area, increase the frictional losses and distort the pressure distribution profile. The influences of flow blockage cover the thermodynamic, aerodynamic and rotordynamic performance parameters of centrifugal compressor as will be investigated further in this study. Accordingly, this paper introduces a novel approach to model the impact of non-reactive deposits flow on the centrifugal compressor aerothermodynamics performance. The developed set of empirical equations in this study provides a new way to derive the equivalent compressor performance map at various degrees of fouling with a consideration of gas properties and stage efficiency variation and without a prior knowledge of the detailed geometrical features. In order to emphasize the validity of the new method, it has been tested with two operating cases and the obtained results were compared with the internal inspection findings from the stage overhauling process. Besides, this approach has been proven to be valid for the modelling of flow blockage effect at the suction side, compressor internals and downstream equipment. Furthermore, a new methodology has been established to assess the possibility of deposits accumulation in the gas path of the compression system based on the operational data of the discharge parameters. Highlights: Novel method to model the impact of non-reactive deposits on compressor performance. The obtained results were compared with the internal inspection findings. Model the flow blockage effect at suction and discharge sides and stage internals. It can be used for operation diagnosis of centrifugal compressors. New methodology to assess the contribution of flow blockage based on available operational data.